JAMINAN HAK NAFKAH ANAK PASCA PERCERAIAN PERSPEKTIF FIKIH SYAFI’IYAH DAN MAQAŞID AL-SYARI’AH - Mawaddah, Lailatul; Zulfadli, Zulfadli (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
Children are a mandate and sustenance from God whose presence is expected by every couple. Children have certain rights, both rights that are material needs and the right to social interaction. One of the children’s rights that are very important to be fulfilled by their parents is the right to life. Imam Syafi’i limits the obligation to provide for children until the age of puberty, while in the KHI it states until the age of 21 years. Therefore, the author wants to take the middle line by looking at the benefits generated through the review of Maqaşid al-Syari’ah. The formulation of the problem from this research is how the guarantee of children’s livelihood rights after divorce from the perspektive of Syafi’iyyah Fiqh and Maqaşid al-Syari’ah? The purpose of this study is to try to explain the child’s right to support after divorce from the perspective of Syafi’iyah Fiqh and Maqaşid al-Syari'ah. The type of research used in this thesis is library research in the form of qualitative. Sources of data from this study came from the books of the Syafi’iyah scholars and books that discussed Maqaşid al-Syari'ah as well as books and journals related to the issue of children’s livelihood rights. The method of data collection was carried out by documentation and the method of data analysis was in the form of qualitative descriptive. The results showed that the Syafi’iyah Ulama stated that the age limit for providing maintenance by parents to children was up to puberty or the age of 15 (fifteen) years. Based on the considerations of Maqaşid al-Syari'ah, applying the age of 22-23 years within the age limit still being provided by parents is a logical provision according to the current situation and conditions.